Falling-droplet-enhanced filmwise condensation in the presence of non-condensable gas. (September 2019) - Wen, Rongfu; Zhou, Xingdong; Peng, Benli; Lan, Zhong; Yang, Ronggui; Ma, Xuehu
Highlights: Hybrid-patterned copper surface with interval fluorocarbon-coated hydrophobic bumps. Falling-droplet-enhanced filmwise condensation is achieved on the hybrid surface. Improved nucleation, condensate removal, and vapor transport across boundary layer. High-performance vapor condensation heat transfer in the presence of NCG is obtained. Abstract: Enhancing condensation heat transfer in the presence of non-condensable gas (NCG) is of fundamental importance for a wide range of energy-intensive industrial applications. Heat transfer performance of vapor condensation in the presence of NCG is dominated by the initial nucleation and mass transfer of vapor molecules in the diffusion layer near the condensing surface. Most of the approaches based on accelerating condensate liquid removal cannot effectively improve the nucleation and vapor transport, which makes it challenging to enhance vapor condensation in the presence of NCG. Here, we present a hydrophilic copper surface with interval fluorocarbon-coated hydrophobic bumps to enable falling-droplet-enhanced filmwise condensation in the presence of NCG. Benefiting from the reduced nucleation energy barrier on the hydrophilic surface, water vapor can rapidly nucleate and form a thin liquid film on the surface. Such condensate film can be periodically removed from the interval hydrophobic bumps to prevent the thickness growth of liquid film along the vertical surface, which is attributed to the surface adhesion reduction of condensate liquid on the hydrophobic bumps. More importantly, the removed condensate liquid departing from the hydrophobic bumps can fall off in the form of droplets to strongly disturb the NCG diffusion boundary layer. Numerical calculations and visualization experiments quantitatively reveal that the falling droplets can significantly improve water vapor transport from the bulk vapor to condensing surface for droplet growth. High-performance heat transfer of the enhanced filmwise condensation in the presence of NCG is experimentally demonstrated to be better than both the conventional filmwise and dropwise condensation while avoiding the durability issues of ultra-thin hydrophobic coatings by utilizing durable fluorocarbon-coated bumps.